The Trepidation Amid Non-Muslims in Afghanistan: A Critical Analysis of the Apprehension Confronted by the Religious Minorities in Taliban’s Rule - Shah, Syed Sibtain Hussain; Khatoon, Sara; Ali, Lubna Abid (Journal of Nautical Eye and Strategic Studies, 2024)
This study examines the concerns of non-Muslim religious minorities in Taliban rule in Afghanistan since 2021. As the Taliban returned to power, fear had particularly increased among Sikhs, Hindus, Christians, and other communities who were already marginalized and facing significant challenges to their survival in the country. The rigid religious laws adopted by the Taliban current regime, combined with its previous harsh policies and resurgence of other militant groups such as Islamic State Khurasan Province (ISKP) and lack of protective measures, has fuelled worries over the safety and rights of these non-Muslim minorities. Studying contemporary incidents of frequent violence and prejudice, and the background of the persecution as a guideline, this paper seeks to investigate the social, religious, and traditional factors involving concerns among minorities.